Interdependent Relationship Between Contrastive Analysis And Translation (Journal of the College of Basic Education, 2022)
Contrastive studies play an important role in the field of language teaching and translation. Since the former is beyond the study of this paper, the present study focuses on the relationship between contrastive analysis (henceforth CA) and translation, i.e., how CA can serve translation and how translation can serve CA.Therefore, the aim of this paper is to find the areas in which CA can take benefit from translation and vice versa because this use is of a great help for both fields. The area whereby translation can make use of CA is the bilingual grammars and bilingual dictionaries which can help translators to perform the process of translation.On the other hand, translation can serve CA by providing contrastivists with the closest translation equivalences that meet their needs in the two areas they are interested with, viz, comparison and contrastiveness, i.e., arriving at similarities or constants and differences between two or more languages respectively.